The Bias of Communication - HAROLD A. INNIS (University of Toronto Press, 2008)
THIS volume includes revisions of papers published elsewhere. They are brought together for purposes of accessibility and to support in more detailed fashion the thesis developed in Empire and Communications (Oxford, 1950). In a sense they are an attempt to answer an essay question in psychology which the late James Ten Broeke, Professor of Philosophy in McMaster University, was accustomed to set, "Why do we attend to the things to which we attend?" They do not answer the question but are reflections stimulated by a consideration of it. They emphasize the importance of communication in determining "things to which we attend" and suggest also that changes in communication will follow changes in "the things to which we attend." It is assumed that history is not a seamless web but rather a web of which the warp and the woof are space and time woven in a very uneven fashion and producing distorted patterns. With the bias of an economist I may have extended the theory of monopoly to undue limits, but it is a part of the task of the social scientist to test the limits of his tools and to indicate their possibilities, particularly at a period when he is tempted to discard them entirely. Similarly an extension of cyclical theory may seem to have been carried too far but the neglect of the field of communication in studies of cycles warranted a consideration of the extent to which monopolies of knowledge collapse and extraneous material is lost, to be followed by the prospect of an emphasis on a fresh medium of communication and on a fresh approach. Moreover, the papers are concerned primarily with the political approach and reflect an Anglo-Saxon obsession. They are restricted to consideration of two dimensions of political organizations, on the one hand the length of time over which the organization persists, and on the other hand the territorial space brought within its control, and are perhaps in themselves a product of the instability which they attempt to describe as characteristic of a period in which time has been torn into fragments. At best they are an attempt to enhance an awareness of the disaster which may follow a belief in the obvious. The letter killeth and the concern has been with the diverse means by which different types of letters bring about their deadly results.